Transesterification of Palm Olein to Fatty Acid Methyl Esters (POle-ME) Using Base Catalysts - Ratri Retno Utami; Andri Saputra; Pani Satwikanitya; Muh Wahyu Sya’bani; Warmiati Warmiati; Luthfi Auliya Indahwati; Danuraja Ilmannafia (Journal of Applied Agricultural Science and Technology, 2025)
Palm olein esters are potentially convertible into epoxy oil, which can serve as a plasticizer. Palm olein can be reacted with alcohol in the presence of a base catalyst in a process named transesterification. This study aimed to investigate the application of palm olein to produce fatty acid methyl esters (POLe-ME) using sodium hydroxide and potassium hydroxide as catalysts, which are then evaluated for their potential as plasticizers. The research process involved selecting raw materials based on the iodine and acid numbers. Subsequently, transesterification was conducted using 1% base catalysts. The characterization of POle-ME included evaluating its acid number, iodine number, viscosity, fatty acid composition, and functional groups. The findings indicate that using a molar ratio of oil to methanol of 1:6 and potassium hydroxide as a catalyst achieved the highest yield at 94.99%. The produced POle-ME exhibited a peak at 1436 cm-1, indicating the presence of a methyl ester functional group. The fatty acid composition of POle-ME consisted predominantly of oleic unsaturated fatty acid (C18:1) at 49.13%. Additionally, POle-ME exhibited an iodine number of 60.42, an acid number of 1.395, and a viscosity of 7.16 mPa·s, indicating its potential as a raw material for epoxy oil (plasticizer) production.